Cercyon castaneipennis sp. n., an overlooked species from Europe (Coleoptera: Hydrophilidae) - Vorst, Oscar (Zootaxa, 2009)
Cercyon castaneipennis sp. n. is recognised as a species distinct from C. obsoletus (Gyllenhal). Apart from small differences in the morphology of the aedeagus, both species can be separated by the structure of the mentum, the shape of the antennal club and the structure and colouration of the elytra. Cercyon castaneipennis is currently known from Central Europe and the southern part of North Europe. In the Netherlands, at the western border of its range, it is considered a recent immigrant, as records before the year 2000 are lacking. A lectotype for C. obsoletus is designated.